Ethylene Epoxidation with Nitrous Oxide over Fe–BTC Metal–Organic Frameworks: A DFT Study. Issue 21 (11th October 2016) - Maihom, Thana; Choomwattana, Saowapak; Wannakao, Sippakorn; Probst, Michael; Limtrakul, Jumras
Abstract: The epoxidation of ethylene with N2 O over the metal‐organic framework Fe–BTC (BTC=1, 3, 5‐benzentricarboxylate) is investigated by means of density functional calculations. Two reaction paths for the production of ethylene oxide or acetaldehyde are systematically considered in order to assess the efficiency of Fe–BTC for the selective formation of ethylene oxide. The reaction starts with the decomposition of N2 O to form an active surface oxygen atom on the Fe site of Fe–BTC, which subsequently reacts with an ethylene molecule to form an ethyleneoxy intermediate. This intermediate can then be selectively transformed either by 1, 2‐hydride shift into the undesired product acetaldehyde or into the desired product ethylene oxide by way of ring closure of the intermediate. The production of ethylene oxide requires an activation energy of 5.1 kcal mol −1, which is only about one‐third of the activation energy of acetaldehyde formation (14.3 kcal mol −1 ). The predicted reaction rate constants for the formation of ethylene oxide in the relevant temperature range are approximately 2–4 orders of magnitude higher than those for acetaldehyde. Altogether, the results suggest that Fe–BTC is a good candidate catalyst for the epoxidation of ethylene by molecular N2 O. Abstract : Makin the most of MOFs : The epoxidation of ethylene into ethylene oxide with nitrous oxide on Fe–1, 3, 5‐benzentricarboxylate metal–organic frameworks is studied by density functional calculations with the M06‐L functional.